Misunderstood vegetables : how to fall in love with sunchokes, rutabaga, eggplant, and more - Selengut, Becky (Countryman Press, an imprint of W. W. Norton & Company, 2024)
Go from "what the heck is this" to "how does it taste so good" in this celebration of misfit vegetables.